Analytical consideration and numerical verification of the confined functionally graded porous ring with graphene platelet reinforcement. (October 2019) - Li, Zhaochao; Zheng, Junxing
Highlights: The buckling behavior of the confined FGP–GPL ring is investigated analytically and numerically. Nine cross-combined cases are examined to optimize the best ring to resist buckling. The symmetrical pores and GPL can best improve the bending stiffness of the ring. A small amount of the GPL increases the buckling load dramatically and reduces the weight of the ring. Abstract: The present work is concerned with the stability behavior of the functionally graded porous (FGP) ring with graphene platelet (GPL) reinforcement. The ring is surrounded by an elastic medium and a point load is introduced at the crown position. Assuming no interface friction between the ring and medium, the buckling load of the ring with a "single-lobe" deformation is obtained analytically. Afterward, the numerical examination is developed by comparing the critical buckling load from the numerical and analytical results. The good comparison indicates the analytical solutions are applicable to the nine cases by combining three porous distributions and three GPL dispersion patterns, respectively. It is explored that the combination of symmetrical pores and symmetrical GPL to the mid-surface can resist the highest external load of the confined FGP–GPL ring, and this case is successfully compared with other closed-form expressions for the homogeneous ring without pores and GPL. Finally, the effects of porosity coefficient, and weight fraction of the GPL are examined and discussed in terms of the load capacity, the hoop force, the bending moment, the hoop stress and strain, and the geometric shapes of the GPL.